The Role of Notaries in the Resolution of Agrarian Disputes in Indonesia - Izar, Shohibul; Primananda, Tahega (Dinasti Research, 2025)
This study discusses the role of notaries in preventing land disputes through authentic document creation and the legal limitations they face in resolving land conflicts. The aim of this paper is to identify the contributions of notaries in reducing potential agrarian disputes and explore efforts to support agrarian justice in Indonesia. The methodology used is a descriptive qualitative approach with a literature study, analyzing agrarian law regulations and the role of notaries within this context. The findings indicate that while notaries play a crucial role in dispute prevention through the creation of authentic deeds, there are limitations in their authority and expertise in verifying the legal status of land. This paper also highlights the importance of improving collaboration between notaries and the National Land Agency (BPN) and the digitalization of land documents to enhance transparency and minimize disputes